Phenolic acid content and antioxidative capacity of methanolic extracts from quality Indian mustard genotypes (Journal of Oilseed Brassica, 2026)
Brassica is one of the foremost oilseed crop cultivated in several parts of the world. Its oil is consumable and defatted meal is a good element for use in aquaculture, animal and human diets, which acquires a copious amount of healthenhancing phytochemicals and anticarcinogenic compounds such as glucosinolates and antioxidative principles such as phenolics, flavonoids, vitamin- C & E. The present investigation emphasized on the phenolic content and antioxidative activity in 30 germplasm of Brassica juncea. It is catechizing that methanolic extracts of a defatted meal of PRQ-2005- 11(BE) (24.14 mg/ml) exhibit paramount in-vitro antioxidative property and F3-F4(3) (6.48 mg/g) possessed utmost total phenolic content. Ortho dihidroxyphenol content differ from 0.070 mg/ml (LG 2005-36-1) to 0.323 mg/ml (F3-F4(2)). The reducing power activity was observed to be highest in PLGM-2002-2-7(1.722) followed by PRQ-2005-11-BE (1.674 mg/ ml), DCF4-F5-3 (1.672 mg/ml) in a dose-dependent manner. The predominant free radical-scavenging activity was observed in DCF4-F5(3) (84.27 mg/ml) at the concentration of 800 μg/ml. Whereas the heightened chelating activity was found in PRQ-2005-4(BL) (71.81 mg/ml) followed by PRQ-2004-9 (71.54 mg/ml) and PDLM 2003-9-6 (70.23 mg/ml) at the concentration of 800 μg/ml. Thus the defatted meal of 30 Indian mustard genotypes was found to possess rich antioxidative capacity which further utilized in the preparation of functional foods as a viable food ingredient.